Gonadotropin-Releasing Hormone Stimulate Aldosterone Production in a Subset of Aldosterone-Producing Adenoma. Issue 20 (May 2016) - Kishimoto, Rui; Oki, Kenji; Yoneda, Masayasu; Gomez-Sanchez, Celso E.; Ohno, Haruya; Kobuke, Kazuhiro; Itcho, Kiyotaka; Kohno, Nobuoki
Abstract : Abstract: We aimed to detect novel genes associated with G protein-coupled receptors (GPCRs) in aldosterone-producing adenoma (APA) and elucidate the mechanisms underlying aldosterone production. Microarray analysis targeting GPCR-associated genes was conducted using APA without known mutations (APA-WT) samples (n = 3) and APA with the KCNJ5 mutation (APA-KCNJ5; n = 3). Since gonadotropin-releasing hormone receptor ( GNRHR ) was the highest expression in APA-WT by microarray analysis, we investigated the effect of gonadotropin-releasing hormone (GnRH) stimulation on aldosterone production. The quantitative polymerase chain reaction assay results revealed higher GNRHR expression levels in APA-WT samples those in APA-KCNJ5 samples ( P < 0.05). LHCGR levels were also significantly elevated in APA-WT samples, and there was a significant and positive correlation between GNRHR and LHCGR expression in all APA samples ( r = 0.476, P < 0.05). Patients with APA-WT (n = 9), which showed higher GNRHR and LHCGR levels, had significantly higher GnRH-stimulated aldosterone response than those with APA-KCNJ5 (n = 13) ( P < 0.05). Multiple regression analysis revealed that the presence of the KCNJ5 mutation was linked to GNRHR mRNA expression (β = 0.94 and P < 0.01). HAC15 cells with KCNJ5 gene carrying T158A mutation exhibited a significantly lower GNRHR expression than that in control cells ( P < 0.05). We clarified increased expression of GNRHR and LHCGR in APA-WT, and the molecular analysis including the receptor expression associated with clinical findings of GnRH stimulation. Abstract : Supplemental Digital Content is available in the text